Hubungan Antara Kestabilan Emosi Dengan Kecemasan Berbicara Di Depan Umum - Sugiarto, Andik Devandi; , Taufik Kasturi, S.Psi., M.Si., Ph.D (2017)
The purpose of this study which is to determine the relationship between emotional stability with the anxiety of public speaking, so the authors put forward the hypothesis there is a negative relationship between emotional stability with the anxiety of public speaking. Subjects in this study were students of SMK Space Flight Maospati of 60 students. Sempel retrieval technique is purposive sampling sampling technique with consideration or criteria. Measuring instrument that is used to reveal the research variables that emotional stability and anxiety of public speaking. Analysis of the data in this study using the Statistical Product and Service Solution. Based on the results of analysis there is a negative correlation very significant between emotional stability with the anxiety of public speaking with a correlation coefficient (r) of -0.790; p = 0.000 (p <0.01), which shows that there is a negative correlation is highly significant (p <0.01) between emotional stability with the anxiety of public speaking. The higher the emotional stability, the lower the level of anxiety of public speaking and conversely the lower the emotional stability, the higher the level of anxiety of public speaking to the students. Emotional stability variables have the empirical mean (RE) = 113.88 and the mean hypothetical (RH) = 125 (RE> RH) indicating that the emotional stability on the subject is low. This could be due to lack of guidance of teachers towards the students regarding emsoi stability, so that the student or students less understanding and less skilled in emotional stability of each individual. empirical mean (RE) variable anxiety in public speaking at 139.53 and the mean hypothetical (RH) by 125 (RE> RH) indicating that public speaking anxiety in students is high. This high condition can be seen in the behavior of students who are less able to express their opinions in front of the class. Based on the above discussion it can be seen that the effect on the emotional stability emotional stability on vocational students Maospati Space Flight Iswahjudi Air Force Base. From the analysis of the data found that the effective contribution of emotional stability to anxiety in public speaking by 62.4% shown by the determinant coefficient (r2) of 0.624. This means there are 37.6% of other variables that influence the anxiety of public speaking. . Keywords: emotional stability, anxiety talking, publicly students smk.